Cases of possible job discrimination based on hearing loss - Laroche, C. (Canadian Acoustics, 1994)
Each year, complaints are filed at the Quebec and Canadian Human Rights Commission by individuals who have been refused employment because their hearing sensitivity does not meet the standards required by the employer. This paper presents four recent cases. The first case deals with a young fireman who, after having completed his training in a specialized school, was refused a job based on a unilateral hearing loss which had not been detected before entering the school. The second case relates to a police officer having a unilateral hearing loss which does not meet the criterion of a federal employer. The two last cases refer to two railroad workers who failed the pre-employment hearing examination because they were not allowed to wear their hearing aids during the tests. These four cases are discussed with the purpose of deriving a scheme of analysis which will take into consideration the Human Rights Acts and the current knowledge in the fields of audiology and ergonomics